Políticas para a extensão universitária e sua implementação na UFG: 2006 a 2016 - Batista, Zenilde Nunes (2019)
This research analyzes the public policies directed to the university extension at the Universidade Federal de Goiás – UFG, during the period from 2006 to 2016. The impulse for this investigation arose from the questioning about the government policies and about the practice of institutional actions directed to the actions of extension. Understanding it as one of the tools of the university that is capable of assisting in the process of social transformation, in a preliminary moment we elected theoretical input for understanding the matter, taking it as a component of a network, through which they move different actors, with a view to the construction and sharing of knowledge. Regarding the methodology, the thesis is predominantly in the scope of qualitative research, having as north studies of the STS (Science, Technology and Society) field, as well as those specific on University Extension – its history and its concepts. The quantitative aspect is summarized in the final section, in which we analyze the institutional policies; therefore, we developed this research under mixed methodology. For this, we resorted to bibliographic and documentary research, in addition to data collection. In this endeavor, the internal documents of the Extension and Culture Pro-Rectory were essential, as well as data from the GFU’s electronic extension system. The laws and norms consultation were another important action in the process. The main objective of this thesis was to investigate the impact caused by public extension policies at GFU. Moreover, the main question asks as a response whether there was growth in the extension afforded by those policies. Our initial hypothesis – that adherence to these policies and specific aspects of internal governance provided a high performance in the area of extension at GFU – confirms itself at the end of the research, along with the finding that government initiatives in that period were also reason for such institutional return size. Key-words: University Extension; Public Policies; Education; Social Actors; Governance.